2022
DOI: 10.1053/j.jvca.2021.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Right Ventricle Dilatation in SARS-CoV-2–Related Acute Respiratory Distress Syndrome on Extracorporeal Membrane Oxygenation Support

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 28 publications
(72 reference statements)
1
19
1
Order By: Relevance
“…This notion is confirmed by the observation when, despite preserved LV systolic function, there is a need for venovenous extracorporeal membrane oxygenation (ECMO) mortality in patients with RV dilatation is extremely high, 73% vs. 35% in patients with normal RV dimensions. 10 In our study, despite significantly milder than reported in the ECMO study disease severity, still there was a strong trend (p = 0.069) for RV dilatation in predicting mortality in the multivariate analysis along with positive pressure ventilation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This notion is confirmed by the observation when, despite preserved LV systolic function, there is a need for venovenous extracorporeal membrane oxygenation (ECMO) mortality in patients with RV dilatation is extremely high, 73% vs. 35% in patients with normal RV dimensions. 10 In our study, despite significantly milder than reported in the ECMO study disease severity, still there was a strong trend (p = 0.069) for RV dilatation in predicting mortality in the multivariate analysis along with positive pressure ventilation.…”
Section: Discussioncontrasting
confidence: 53%
“…With the reported prevalence of RVD in COVID-19 patients ranging from 8% to 52%, 1 , 2 , 3 RVD is increasingly recognized as an important indicator of COVID-19 severity and adverse outcomes associated with severe COVID-19. 10 The exact mechanisms of RVD in COVID-19 remain under investigation and it continues to be unclear whether RVD is a marker of COVID-19 lung injury causing acute RV pressure overload or whether RVD is independent of the lung disease process. 4 It has been suggested that primary RVD may be due to direct myocardial injury from COVID-19 viral myocarditis, hypoxia, inflammatory response, and/or autoimmune injury.…”
Section: Discussionmentioning
confidence: 99%
“…One group was characterized by RV dysfunction: all these patients died because of unfavorable progression of COVID pulmonary disease characterized by bilateral pulmonary consolidations. The second group showed higher values of left ventricular ejection fraction and normal RV dimensions and function, but these patients died from septic shock [7] .…”
Section: The Clinical Role Of Right Ventricle Changes In Covid Respiratory Failure Depends On Disease Severitymentioning
confidence: 91%
“…Serial echocardiography and an appreciation of the characteristic features of COVIDinduced respiratory failure may provide insights. As discussed by Dandel [2,6] and others [7,8], RV dilatation and dysfunction reflect and follow COVID-induced pulmonary thrombotic microangiopathy, a feature recognized as a characteristic pattern of COVID disease [9,10] . Thus, RV dilatation and dysfunction may be considered a marker of COVID disease severity, but may not fully explain why these changes are not directley related to mortality, especially in the critically ill patients [4,5].…”
Section: The Clinical Role Of Right Ventricle Changes In Covid Respiratory Failure Depends On Disease Severitymentioning
confidence: 95%
See 1 more Smart Citation